Müller glia cell reprogramming and retina regeneration - Goldman, Daniel (Nat Rev Neurosci, 2014)
Müller glia are the major glial component of the retina. They are one of the last retinal cell types to be born during development and they function to maintain retinal homeostasis and integrity. In mammals, Müller glia respond to retinal injury in a variety of ways that can be either protective or detrimental to retinal function. Although under special circumstances these cells can be coaxed to proliferate and generate neurons, these responses are meager and insufficient for repairing a damaged retina. By contrast, in teleost fish (such as zebrafish) the response of Müller glia to retinal injury involves a reprogramming event that imparts retinal stem cell characteristics and allows them to produce a proliferating population of progenitors that can regenerate all major retinal cell types and restore vision. Recent studies have revealed a number of important mechanisms underlying Müller glia reprogramming and retina regeneration in fish that may lead to new strategies for stimulating retina regeneration in mammals.